Carbon footprint calculator for a typical campus in Malaysia using life cycle assessment approach - Daud, Noorol Jannah (2012)
In the history of climate change issue, human activities have been documented as a devotee in accelerating the increase number of greenhouse gases (GHGs) in the atmosphere. The subject has grown in importance to estimate and monitor GHGs emission from various activities. In this study, Information Communication Technology-based (ICT-based) software is developed to estimate GHG from campus activities since there is no interactive calculator yet to reliably measure it. The GHGs evaluation is performed using gateto gate life cycle system boundary. Normalization for population and total building space occupied were used to represents the distribution of carbon emissions for different sources over time period. The data from various activities in Universiti Teknologi Malaysia (UTM) includes electricity, transportation, wastewater, solid waste, and fertilizer for 2 years period (2009-2010) is used to evaluate the effectiveness of the carbon calculator. It was found that the results obtain from the carbon calculator is agreed with the sustainable initiative in UTM.